Clinical Features of Urticaria: Results From a Hospital-Based Multicenter Study in China - Wang, Xin; Liu, Li-Juan; Li, Lin-feng; Shi, Xiao-Dong; Shen, Yi-Wei (Frontiers in Medicine, 2022)
Background: The clinical features of urticaria have not been fully illustrated. Objectives: To demonstrate clinical features of urticaria in different areas of southern and northern in China. Methods: In this hospital-based multicenter study, urticaria outpatients filled in a questionnaire at initial visit and follow-up (once per week, lasting for a month). Results: Overall, 1715 urticaria outpatients were recruited with a mean age of 37.86 ± 16.08 years (range, 0.5-87 years). The median disease duration was 1.94 ±4.31 years (range, 0-58 years). More itching was observed in the north higher than that of in the south (99.5% vs 94.1%, P < 0.001). The incidence of pain, arthralgia and family history in southern areas is higher than that in northern (5.1% vs 1.1%, 9.6% vs 0%, 10.6% vs 3.2%, P<0.001). The leading subtypes of specified urticaria were chronic spontaneous urticaria (81.4%) and symptomatic dermographism (35.9%). The incidence of symptomatic dermographism and cold urticaria in the south was lower than that in the north (31.8% vs. 50.3%, 4% vs. 8.5%, P<0.001). Allergic diseases were the most common concomitant disorders of urticaria. More than half of patients had to avoid certain food, such as fish-prawn-crab (30.7%) and alcohol (20%). Ebastine (41.1%) was the most commonly prescribed drugs. The disease duration negatively correlated with severe itching and quantity of wheal (>50/24H) (Spearman’s rank correlation test, P < 0.001). Conclusions: this study provides a profile of clinical characteristics of urticaria in China, and filled the gap in the field of regional comparative studies on urticaria.